Deciphering the transcriptomic landscape of systemic lupus erythematosus-associated pulmonary arterial hypertension - Li, Yutong; Qian, Junyan; Deng, Xiaoyue; Ma, Leyao; Yuan, Qizhi; Wang, Qian; Tian, Zhuang; Zeng, Xiaofeng; Yang, Xinzhuang; Zhao, Jiuliang; Li, Mengtao (Respiratory research, 2025)
Systemic lupus erythematosus (SLE) is an autoimmune disease that involves multi-organ damage. Pulmonary arterial hypertension (PAH) is one of the life-threatening complications of SLE. The underlying cause of systemic lupus erythematosus-associated pulmonary arterial hypertension has not been fully comprehended. Besides the mechanisms implicated in the development of PAH, such as damage to the endothelial cells, the aberrant activation of the immune system also plays a substantial role in the pathogenesis of SLE-PAH. In this study, peripheral blood samples from 100 patients with SLE-PAH and 95 patients of SLE without PAH (SLE-nonPAH) were obtained for RNA sequencing and comprehensive transcriptomic analysis. Pathway enrichment analysis was performed based on differentially expressed genes (DEGs) between SLE-PAH and SLE-nonPAH to elucidate the mechanisms potentially driving the development of PAH in SLE patients. Utilizing consensus non-negative matrix factorization (cNMF), we also conducted a detailed analysis to identify distinct subgroups within the SLE-PAH population. Meanwhile, the protein-protein interaction (PPI) analysis was performed and hub genes among the SLE-PAH subgroups were detected. Common transcription factors (TFs) of detected hub genes were also discovered to serve as potential therapeutic targets. Inflammatory signaling pathways, notably those involving interferon and TNFα, were found to play an important role in the SLE-PAH. Utilizing cNMF method, three unique subgroups of SLE-PAH patients were delineated, each characterized by a distinct level of inflammatory activity. Specifically, the high inflammation subgroup, marked by the activity of Interleukin-6 (IL-6), exhibited a milder form of PAH. In contrast, the subgroup with moderate inflammation displayed the most pronounced PAH symptoms. Further disease enrichment analysis revealed that, beyond the dysregulated inflammatory pathways, patients with the most severe PAH exhibited distinct pathogenic transcriptomic profiles that disrupted vascular smooth muscle homeostasis, a critical component of vascular health. In the most severely affected subgroup, 13 hub genes were identified. Additionally, two transcription factors commonly associated with these genes, KLF1 and GATA1, were discovered, which may serve as potential therapeutic targets. Our investigation establishes inflammation as a key driver in the development of SLE-PAH. Patients who presented with concurrent dysregulations in inflammatory responses along with PAH-specific pathogenic markers exhibited a marked increase in the severity of their PAH. The insights gleaned from our transcriptomic analysis reveal the intricate interplay between inflammatory mechanisms and the molecular substrates of PAH. This nuanced understanding paves the way for more targeted and effective therapeutic approaches for SLE-PAH.